Prevalence and correlation of depression among thyroid disorder patients in Malaysia - Jaafar, Siti Nur Illiani; Daud, Azlina; Saidi, Sanisah; Musa, Ramli; Nik Ahmad, Nik Nur Fatnoon (2019)
Patients with thyroid disorders were found to experience depression due to several factors. The aims of this study is to measure prevalence of depression among thyroid disorder patients and find the correlation between depression and Thyroid Stimulating Hormone (TSH) and free Thyroxine (fT4), stressful life events and social support level. A cross sectional study was carried out at one of the non-profit hospital at central region of Peninsular Malaysia. Several tools used in this study including Depression Anxiety Stress Scale-42 (DASS-42) was selected to determine the level of depression, list of Life Threatening Experiences (LTE) to identify the stressful life events, Multidimensional Scale of Perceived Social Support (MSPSS) to determine the level of social support; and Thyroid Function Test including TSH and fT4 were reviewed from the patient’s file. About 15% (n=23) patients had varies degree of depression (males - 7.8% (n=3) and females – 17.3% (n=20)). Also, there were positive correlation between depression and TSH (r=0.235, p=0.03) and stressful life events (r=0.264, p=0.001). These findings suggested that thyroid disorder patients had experience depression and correlated with TSH level and stressful life events.